2010
DOI: 10.1152/advan.00094.2009
|View full text |Cite
|
Sign up to set email alerts
|

Insights into digestion and absorption of major nutrients in humans

Abstract: Nutrient digestion and absorption is necessary for the survival of living organisms and has evolved into the complex and specific task of the gastrointestinal (GI) system. While most people simply assume that their GI tract will work properly to use nutrients, provide energy, and release wastes, few nonscientists know the details about how various nutrients are digested and how the breakdown products traverse the cells lining the small intestine to reach the blood stream and to be used by the other cells of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
175
0
23

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(201 citation statements)
references
References 10 publications
3
175
0
23
Order By: Relevance
“…Comparably, the grass carp genes involved in the GCSD were not only associated with immune-related genes but also with development-related genes ( Fig. 3 and Supplementary Table 15) and were involved in cell proliferation and differentiation (for example, the focal adhesion pathway and the extracellular matrix (ECM)-receptor interaction pathway 30,31 ), nutritional homeostasis (for example, the protein digestion and absorption pathway 32,33 ) and organ size control (for example, the Hippo signaling pathway 34,35 ). Comparison of genes involved in the overview maps of metabolism (reference map ko01100 of the KEGG database) also indicated that grass carp genes involved in the GCSD clustered in carbohydrate metabolism and nucleotide metabolism (Supplementary Fig.…”
Section: Evolutionary Analysismentioning
confidence: 99%
“…Comparably, the grass carp genes involved in the GCSD were not only associated with immune-related genes but also with development-related genes ( Fig. 3 and Supplementary Table 15) and were involved in cell proliferation and differentiation (for example, the focal adhesion pathway and the extracellular matrix (ECM)-receptor interaction pathway 30,31 ), nutritional homeostasis (for example, the protein digestion and absorption pathway 32,33 ) and organ size control (for example, the Hippo signaling pathway 34,35 ). Comparison of genes involved in the overview maps of metabolism (reference map ko01100 of the KEGG database) also indicated that grass carp genes involved in the GCSD clustered in carbohydrate metabolism and nucleotide metabolism (Supplementary Fig.…”
Section: Evolutionary Analysismentioning
confidence: 99%
“…SCFA epitel hücrelere enerji sağlar, kemoterapi gibi stres durumlarda iltihaplanmayı azaltır, epitel hücre gelişmesini destekler, bağırsakların zarar görmesini engeller ve bağırsak geçirgenliğini arttırarak kalsiyum ve magnezyum emilimini iyileştirir (Ziegler ve Evans, 2003;Parodı, 2009;Jacobi ve Odle, 2012). (Hinsberger ve Sandhu, 2004;Jackson ve McLaughlin, 2009;Goodman, 2010;Boudry ve ark., 2010;Yeap ve ark., 2013).…”
Section: Lipitlerin Sağlık Açısından öNemiunclassified
“…Tüm bunlara ek olarak safra kesesinden günde 10-15 g fosfolipit ve 1-2 g endojen kolesterol salgılanmaktadır. Ayrıca sindirim kanalında dökülen ölü epitel hücreler ve ölü bakteri hücreleri kaynaklı endojen membran lipitler ve fosfolipitler de organizmaya günde 40-60 g lipit sağlamaktadır (Hinsberger ve Sandhu, 2004;Jackson ve McLaughlin, 2009;Yong ve ark., 2009;Boudry ve ark., 2010;Goodman, 2010;Jacobi ve Odle, 2012;Rein ve ark., 2012).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Many of them can form gels that will constitute their structure and also enhance viscosity of solutions owing to their high molecular weight (Aguilera & Stanley, 1999). Although carbohydrates are not essential in the diet, they generally make up ~40-45% of the total daily caloric intake of humans, with plant starches generally comprising 50-60% of the carbohydrate calories consumed (Goodman, 2010). Hence, starch becomes the most important source of energy in the human diet.…”
Section: Starchmentioning
confidence: 99%